Association of Overlapping, Nonconcurrent, Surgery With Patient Outcomes at a Large Academic Medical Center: A Coarsened Exact Matching Study. Issue 4 (October 2019) - Glauser, Gregory; Osiemo, Benjamin; Goodrich, Stephen; McClintock, Scott D.; Vollmer, Charles; DeMatteo, Ronald; Malhotra, Neil R.
Abstract : Objective: Assess the safety of overlapping surgery before implementation of new recommendations and regulations. Background: Overlapping surgery is a longstanding practice that has not been well studied. There remains a need to analyze data across institutions and specialties to draw well-informed conclusions regarding appropriate application of this practice. Methods: Coarsened exact matching was used to assess the impact of overlap on outcomes amongst all surgical interventions (n = 61, 524) over 1 year (2014) at 1 health system. Overlap was categorized as: any, beginning, or end overlap. Study subjects were matched 1:1 on 11 variables. Serious unanticipated events were studied including unplanned return to operating room, readmission, and mortality. Results: In all, 8391 patients (13.6%) had any overlap and underwent coarsened exact matching. For beginning/end overlap, matched groups were created (total matched population N = 4534/3616 patients, respectively). Any overlap did not predict unanticipated return to surgery (9.8% any overlap vs 10.1% no overlap; P = 0.45). Further, any overlap did not predict an increase in reoperation, readmission, or emergency room (ER) visits at 30 or 90 days (30D reoperation 3.6% vs 3.7%; P = 0.83, 90D reoperation 3.8% vs 3.9%; P = 0.84) (30D readmission 9.9% vs 10.2%; P = 0.45, 90D readmissions 6.9% vs 7.0%; P = 0.90) (30D ER 5.4% vs 5.6%; P = 0.60, 90D ER 4.8% vs 4.7%; P = 0.71). In addition, any overlap was not associated with mortality over the surgical follow-up period (90D mortality 1.7% vs 2.1%; P = 0.06). Beginning/end overlap had results similar to any overlap. Conclusion: Overlapping, nonconcurrent surgery is not associated with an increase in reoperation, readmission, ER visits, or unanticipated return to surgery. Abstract : Supplemental Digital Content is available in the text